The Clinical Features of Co-circulating Dengue Viruses and the Absence of Dengue Hemorrhagic Fever in Pakistan - Khan, Erum; Prakoso, Dhani; Imtiaz, Kehkashan; Malik, Faisal; Farooqi, Joveria Q.; Long, Maureen T.; Barr, Kelli L. (Frontiers in Public Health, 2020)
1 Dengue virus (DENV) is the most common and widespread arboviral infection worldwide. Though all four DENV serotypes cocirculate in nature, the clinicopathological framework of these serotypes is undefined in Pakistan. A cross-sectional, observational study was performed to document the circulation of various arboviruses in the Sindh region of Pakistan. Here we describe a population of patients diagnosed with DENV spanning a 2-year period. A total of 168 NS1 positive patients were recruited of which 91 patients were serotyped via RT-PCR. There was no significant difference between sex or age for infection risk and peak transmission occurred during the Autumn months. DENV2 was the most common serotype followed by DENV1 then DENV3, then DENV4. The data show that DENV1 had the greatest impact on the liver with higher frequency of abnormal liver function tests; DENV2 affected the central nervous system and joints; DENV3 affected the urinary system and blood; and DENV4 caused headaches and rash. Notably no dengue hemorrhagic fever or other manifestations of severe dengue fever were present in patients with primary or secondary infections. This study used an orthogonal system of NS1 antigen ELISA followed by RT-PCR for DENV detection and subtyping. We were able to identify significantly more NS1 antigen positive patients than RT-PCR. This study demonstrates that all four DENV serotypes are co-circulating and co-infecting in Pakistan.